A Statewide Evaluation of the California Medical Supervision Program Using Cholinesterase Electronic Laboratory Reporting Data - Ouahiba Laribi PhD; Brian Malig MS; Katherine Sutherland-Ashley PhD; Rachel Broadwin MS; Walker Wieland BS; Charles Salocks PhD (SAGE Publishing, 2017)
The California Medical Supervision program is designed to protect workers who regularly mix, load, or apply the highly toxic Category I and II organophosphates and carbamates from overexposure by monitoring cholinesterase (ChE) inhibition in plasma and red blood cells. Since January 2011, testing laboratories are required to report test results electronically to the California Department of Pesticide Regulation who shares it with the Office of Environmental Health Hazard Assessment for evaluation. The purpose of this study is to assess the utility of this reporting in evaluating the effectiveness of the Program for illness surveillance and prevention. From 2011 to 2013, we received more than 90 000 test results. Despite data gaps and data quality issues, we were able to perform spatial and temporal analyses and developed a screening tool to identify individuals potentially at risk of overexposure. The data analysis provided some evidence that the Program is effective in protecting agricultural workers handling the most toxic ChE-inhibiting pesticides even though it also identified some areas of potential concerns with individuals that appeared lacking corrective actions in the workplace in response to excessive ChE depressions and parts of the state with disproportionately at-risk individuals. However, changes to the electronic reporting are needed to more accurately identify tests related to the Program and therefore improve the utility of the data received. Moreover, data analysis also revealed that electronic reporting has its limitation in evaluating the Program.